2015
DOI: 10.1044/2015_aja-14-0065
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review on the Diagnostic Accuracy of Hearing Screening Instruments for Preschool- and School-Age Children

Abstract: Both pure-tone and OAE screening can identify hearing loss in preschool- and school-age children. Studies that compared both tools in the same population concluded that pure-tone screening had higher sensitivity than OAE screening and thus was considered the preferred tool. Future research should incorporate standard stimulus levels, response criteria, and definitions of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 37 publications
0
46
0
8
Order By: Relevance
“…An evidence-based literature review of eight studies for pure-tone screening tests for children reported sensitivities of 0.12% – 97% and specificities of 0.5% – 99%. Definitions of hearing loss, response criteria and technologies used varied between the eight studies reported (Prieve, Schooling, Venediktov, & Franceschini, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An evidence-based literature review of eight studies for pure-tone screening tests for children reported sensitivities of 0.12% – 97% and specificities of 0.5% – 99%. Definitions of hearing loss, response criteria and technologies used varied between the eight studies reported (Prieve, Schooling, Venediktov, & Franceschini, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…39-41 Prieve et al 42 conducted a systematic review on the diagnostic accuracy of hearing screening instruments for preschool and school-aged children. The findings of the study revealed that pure-tone audiometry screening has a high sensitivity and is considered the preferred tool when compared to other tests such as otoaccoustic emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing: All participants were screened through an otoacoustic emissions (OAE) hearing test (validated as a tool for screening for hearing loss) 13 . Participants who failed this test in both ears or for whom a reading could not be taken underwent…”
Section: Screening For Other Impairmentsmentioning
confidence: 99%